Analisis Kebutuhan Poster Dengan QR-Code sebagai Media Pembelajaran Sejarah pada Materi Pemerintahan Darurat Republik Indonesia (PDRI) untuk SMA - Gusmita, Mia; Hastuti, Hera (YASIN, 2024)
This research aims to analyze the needs for developing history learning media at SMA Negeri 1 Payakumbuh District for class XI Phase F students. The research method used by researchers is a qualitative descriptive method. Data collection techniques include conducting interviews and observations in the field. Furthermore, in this research, researchers carried out several stages of analysis, starting from analyzing the needs of students, teachers, to the independent curriculum. The results of research on needs analysis showed that problems regarding students' interest and enthusiasm in the history learning process were still low. Resulting in ineffective learning processes and low student understanding of the historical events they are studying. As a result, history learning becomes boring and monotonous and the learning process also lacks the use of media that attracts students' interest in the learning process. So, a media innovation is needed that can increase students' interest and enthusiasm in learning history. The media used as a solution in this research is the development of Poster media with QR-Code, in which images, videos and materials are presented, which are expected to increase interest and enthusiasm in learning history for students. Therefore, the objectives of learning history can be achieved optimally.